2020
DOI: 10.1038/s41598-020-59489-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitis vinifera polyphenols from seedless black fruit act synergistically to suppress hepatotoxicity by targeting necroptosis and pro-fibrotic mediators

Abstract: Human is subjected from his surrounding to various hepatotoxins, which aggravates his liver. nowadays, natural polyphenols have attracted great interest in health improvement, especially liver health. the present research, therefore, assessed the hepatotherapeutic potency of the isolated polyphenols (VVF1) from seedless (pulp and skin) black Vitis vinifera (VV) against CCl 4 -induced hepatotoxicity in vitro and in vivo. Further, VVF1 was fractionated into resveratrol-enriched (VVF2) and phenolics-enriched (VVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…The obtained synergism between DMSA and BVJ may be related to their antioxidant properties. As several studies have shown synergistic antioxidant and anti-inflammatory impacts after the combination of different antioxidant extracts or drug and extract [18,34,53]. However, the exact mechanism for this synergism needs further investigations and analyses.…”
Section: Phytochemical Compoundmentioning
confidence: 97%
“…The obtained synergism between DMSA and BVJ may be related to their antioxidant properties. As several studies have shown synergistic antioxidant and anti-inflammatory impacts after the combination of different antioxidant extracts or drug and extract [18,34,53]. However, the exact mechanism for this synergism needs further investigations and analyses.…”
Section: Phytochemical Compoundmentioning
confidence: 97%
“…This can be due to the liver's metabolism, which is caused by CYP2E1. This catabolic process resulted in the formation of CCl 3 *, which converted to the additional reactive trichloromethyl peroxyl radical (CCl 3 OO*), following its combination with oxygen 2,24 . Formation of these radicals will augment the ROS level in the liver and induce a disruption of its redox state and in turn, cause the occurrence of the oxidative stress, leading to hepatic damage.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these compounds explains the current outcomes about the antioxidant activities of AS in vitro through scavenging the ABTS, NO, and lipid peroxide radicals. Hence, the antioxidant activities of the phenolic acids and reducing sugars were reported extensively in the previous researches 2,19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations